1992
DOI: 10.1093/jmedent/29.5.796
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Male Mating Response and Female Flight Sounds in Aedes aegypti and Ae. albopictus (Diptera: Culicidae)

Abstract: Aedes aegypti (L.) and Ae. albopictus (Skuse) showed similar rates and timing of insemination in the laboratory. Laboratory attempts at interspecific mating were unsuccessful. Because Ae. aegypti males are known to locate females by flight sounds, male response to sound was compared in the two species. Ae. aegypti males responded to female flight sounds with stereotypical orientation and mating behavior, whereas Ae. albopictus males seldom responded. Recorded flight sounds of females were sampled via computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…aegypti males did not increase, and may have decreased, when a frequency of 465 Hz was used instead of 440 Hz, which contradicts previous lab-based studies that indicated an optimal response of Ae. aegypti to tones close to 465 Hz (Ikeshoji 1981, Duhrkopf andHartberg 1992). A subject of further investigation would be whether the higher numbers we caught at 440 Hz reßect a difference in behavior of the Ae.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…aegypti males did not increase, and may have decreased, when a frequency of 465 Hz was used instead of 440 Hz, which contradicts previous lab-based studies that indicated an optimal response of Ae. aegypti to tones close to 465 Hz (Ikeshoji 1981, Duhrkopf andHartberg 1992). A subject of further investigation would be whether the higher numbers we caught at 440 Hz reßect a difference in behavior of the Ae.…”
Section: Discussionmentioning
confidence: 91%
“…Males were transferred gently by mouth aspirator to a small plastic Dixie cup (Dixie Consumer Products, Atlanta, GA) covered with netting. Individual males were then presented with a generated tone by placing a speaker (JBuds, JLab Audio, Oceanside, CA) on top of the netting and playing a tone from an "iPod" mp3-player (Apple, Cupertino, CA) for 10 s. A response was scored as positive if the male ßew to the speaker and pressed his terminalia to the netting as if copulating (Duhrkopf and Hartberg 1992). The tones used in all experiments were generated using Audacity (http://audacity.…”
Section: Methodsmentioning
confidence: 99%
“…albopictus because these organs assume sex-specific roles in this species. Both sexes produce and recognise each other through courtship sounds (Duhrkopf & Hartberg 1992) and the females must fly with precision to feed quickly on a host that is awake. These behaviours could result in sex-specific differences in selective pressures; thus, sexual selection cannot be discarded within this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for this conclusion was the observation that males of many species respond to female flight tones by flying towards the source of sound ( Charlwood & Jones 1979 , Duhrkopf & Hartberg 1992 , Belton 1994 , Clements 1999 ) and males have more “plumose” antennae (i.e., many more fibrillae or “hairs” on each antenna), creating a greater surface area with which to detect sound ( Belton 1994 , Clements 1999 ). Gibson and Russell (2006) were the first to show, using Toxorhynchites brevipalpis mosquitoes, that females also respond to male flight tones, albeit not by altering their flight course.…”
mentioning
confidence: 99%